(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
The main purpose of the study was to understand the extent of awareness of farmers on use of ICT in farm practices. At the same time, important factors were identified those could contribute to farmers‟ awareness on use of ICT. The study was conducted in the existing CIG of Ishwarganj upazila in Mymensingh district. Data were collected from 110 CIG farmers in the selected upazila during the period from 03 October to 05 November, 2018 by using a pre-tested structured interview schedule. Farmers‟ awareness was measured by checking extent of their extent of awareness of seven selected ICT services as cell phone, smart phone, personal computer, services from AICC, services from UDC, Krishi Call Centre and mobile apps. A number of characteristics of the farmers were selected as the factors for explaining farmers‟ awareness on use of ICT. Appropriate scales were developed and used in order to measure the concerned variables. Correlation test was used to ascertain the relationships between the concerned variables, while multiple regression (enter method) analysis was also used to determine the contributions of the farmers’ selected characteristics to their opinion on selected ICT based facilities. Results showed that 23.7 percent farmers had “moderate awareness” on use of ICT in farm practices while 60 percent and 12.7 percent of the farmers had “low” and “very low awareness” on use of ICT based facilities in their farm practices. Farmers’ characteristics such as education, knowledge about ICTs, ability to use ICTs, access to ICT facilities, attitude towards ICT had significant positive relationship with their awareness on use of ICT; while age, household size and annual income had significant negative relationship with the awareness on use of ICT. Results of multiple regression analysis revealed that the influential factors on the farmers‟ awareness on use of ICT were household size, knowledge about ICT, ability to use ICT and attitude towards ICT. The R2 value indicated that, four explanatory variables together explained 80.0 percent variation infarmers‟ awareness on use of ICT. The study also identified some constraints faced by the farmers while using ICT services in receiving agricultural information. The study revealed that an overwhelming majority of the farmers (97.3 percent) had high level problems in using ICTs while only 2.7 percent faced medium problems. Lack of training facilities on ICT, cost of using ICT services, low knowledge on availability of ICT based facilities, lack of operational knowledge of computer, low bandwidth speed of internet, limited availability of ICT services, poor level of education/ illiteracy, and so on were identified as the major constraints faced by the farmers. Asian Australas. J. Biosci. Biotechnol. 2019, 4 (1), 34-47